A mathematical structure relating situation knowledge to performance. (4th July 2018) - Landry, Steven J.
ABSTRACT: The linguistic conjecture that a person's knowledge regarding a situation affects some aspects of that person's performance at a task is translated into a mathematical structure. The structure contains a symbolic representation of the conjecture, along with a symbolic definition of what type of knowledge constitutes 'situation' knowledge. The structure is applied to a short example to demonstrate its use. The translation of the conjecture into a mathematical structure enables researchers to use a consistent, objective framework for testing hypothesised relationships between one's situation knowledge and performance, as well as enables mathematical tools to be applied to the study of this conjecture.